Nanoscale x-ray investigation of magnetic metallofullerene peapods. (2nd October 2017) - Fritz, Fabian; Westerström, Rasmus; Kostanyan, Aram; Schlesier, Christin; Dreiser, Jan; Watts, Benjamin; Houben, Lothar; Luysberg, Martina; Avdoshenko, Stanislav M; Popov, Alexey A; Schneider, Claus M; Meyer, Carola
Abstract: Endohedral lanthanide ions packed inside carbon nanotubes (CNTs) in a one-dimensional assembly have been studied with a combination of high resolution transmission electron microscopy (HRTEM), scanning transmission x-ray microscopy (STXM), and x-ray magnetic circular dichroism (XMCD). By correlating HRTEM and STXM images we show that structures down to 30 nm are resolved with chemical contrast and record x-ray absorption spectra from endohedral lanthanide ions embedded in individual nanoscale CNT bundles. XMCD measurements of an Er3 N@C80 bulk sample and a macroscopic assembly of filled CNTs indicate that the magnetic properties of the endohedral Er 3+ ions are unchanged when encapsulated in CNTs. This study demonstrates the feasibility of local magnetic x-ray characterisation of low concentrations of lanthanide ions embedded in molecular nanostructures.